MV-RLU - Jaeho Kim; Ajit Mathew; Sanidhya Kashyap; Madhava Krishnan Ramanathan; Changwoo Min (Proceedings of the Twenty-Fourth International Conference on Architectural Support for Programming Languages and Operating Systems, 2019)
A 5-year-old girl with high-risk neuroblastoma underwent 123I-MIBG SPECT/CT after resection of a right adrenal tumor. Baseline 123I-MIBG imaging showed no abnormal uptake. At 6 months, focal 123I-MIBG accumulation appeared in the left erector spinae muscle, correlating with hypertrophy on CT. By 12 months, uptake had fully resolved, although muscular hypertrophy partially regressed. This illustrates that skeletal muscle hypertrophy, especially post-asymmetric surgery, can cause transient, false-positive 123I-MIBG uptake an\d must be considered in the differential diagnosis of unexpected tracer accumulation.